Controllable synthesis and electrocatalytic applications of atomically precise gold nanoclusters. Issue 22 (18th October 2021) - Zhu, Qingyi; Huang, Xiaoxiao; Zeng, Yunchu; Sun, Kai; Zhou, Linlin; Liu, Yuying; Luo, Liang; Tian, Shubo; Sun, Xiaoming
Abstract : The main synthesis methods and electrocatalytic applications of atomically precise gold nanoclusters are summarized and critically reviewed. The synthesis methods of gold nanoclusters were classified and discussed, and their applications in electrochemistry were introduced. Abstract : Nanoclusters are composed of metal atoms and ligands with sizes up to 2–3 nm. Due to their stability and unique structure, gold nanoclusters with precise atomic numbers have been widely studied. Until now, atomically precise gold nanoclusters have been synthesised by various methods. Common ones include the Brust–Schiffrin method and the size-focusing method. With more detailed research on gold nanoclusters, more novel methods have been adopted to synthesise atomically precise gold nanoclusters, such as anti-galvanic reduction, ligand-exchange reactions from metal nanoclusters, the seed growth method, and so on. Besides, the nanoclusters also have many unique properties in electrochemical catalyses, such as the ORR, OER, etc., which are helpful for the development of the energy and environment. In this review, the synthesis methods and electrochemical applications of atomically accurate gold nanoclusters in recent years are introduced.